Comparison between aluminum and all composite AL5 aircraft fuselage. - Rodolfo Delatore Alonso (2008)
This work demonstrate the decision that lead the responsible team for the AL5 aircraft to recommend more dedicated study, on using composite materials on the constant section barrel of the fuselage, to the next design team. The recommendation where made after the mass comparison of a composite fuselage and an equivalent aluminum fuselage, both estimated through methodologies described on the books of Bruhn and Niu.